Dithienylmethanone‐Based Cross‐Conjugated Polymer Semiconductors: Synthesis, Characterization, and Application in Field‐Effect Transistors. Issue 9 (9th February 2018) - Shi, Keli; Zhang, Weifeng; Wei, Congyuan; Lin, Zuzhang; Liu, Xiaotong; Yu, Gui
ABSTRACT: Herein, we report the synthesis, characterization, and field‐effect properties of two cross‐conjugated dithienylmethanone (DMO)‐based alternating polymers, namely, PDMO‐S andPDMO‐Se . Both polymers possess high thermal stability, good solubility, and broad absorption spectra. Their electrochemical properties were investigated using cyclic voltammetry, indicating thatPDMO‐Se has higher HOMO/LUMO energy levels of −5.49/−3.49 eV than −5.57/−3.58 eV ofPDMO‐S . The two polymers exhibited promising charge transport properties with the highest hole mobility of 0.12 cm 2  V −1  s −1 forPDMO‐S and 0.025 cm 2  V −1  s −1 forPDMO‐Se . AFM and 2D‐GIXRD analyses demonstrated that thePDMO‐S formed lamellar, edge‐on packing thin film with close π ‐ π stacking. These findings suggest that cross‐conjugated polymers might be potential semiconducting materials for low‐cost and flexible organic electronics. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1012–1019 Abstract : Two cross‐conjugated dithienylmethanone‐based alternating polymers, PDMO‐S and PDMO‐Se, were synthesized. PFETs based on the two polymers exhibited p ‐type charge transport characteristics with the highest mobilities of 0.12 cm 2  V −1  s −1 . These findings suggest that cross‐conjugated polymers might be potential semiconducting materials for PFETs.